MAKNA MASA ADVEN DAN RELEVANSINYA BAGI KEHIDUPAN UMAT DI KELOMPOK UMAT BASIS SANTO YOHANES MARIA VIANEY PAROKI SANTO MATIAS RASUL TOFA - Tamelab, Petrus (STIPAS Keuskupan Agung Kupang, 2022)
One of the most urgent times for Catholics is Advent. During this time, Catholics prepare to welcome the coming of Jesus Christ on Christmas. At this time, Catholics reflected on themselves as helpless humans by expressing repentance for the coming of the Messiah. The aim of this research is to interpret the Advent period as a period of preparation and a time of repentance for the people at KUB Yohanes Maria Vianey. The method used in the research is descriptive naturalistic. Naturalistic refers to another name for qualitative methods. It is called naturalistic because the writing was done in the original conditions of the people. Meanwhile, descriptive shows the process of explaining a problem. Based on the results of interviews obtained from 5 informants, it is known that the level of understanding of the people regarding the Advent period is quite good. However, it cannot be denied that some people do not interpret the Advent season as a time of preparation for God's Christmas. During the Advent season there are people who party hard, make noise in the neighborhood and don't even go to church on Advent Sunday. Therefore, one of the efforts offered is community catechesis to help enlighten the congregation about the urgency of the Advent season.